UJI TOKSISITAS EKSTRAK ETANOL 96 % DAUN CINCAU HIJAU (Cyclea barbata Miers) TERHADAP Artemia salina Leach. DENGAN METODE Brine Shrimp Lethality Test (BSLT) - Puspita Sari, Dyah Ratna Ayu (Journal Pharmactive, 2024)
Medicinal plants are one of the efforts used to control disease. The benefits of medicinal plants have been passed down from generation to generation by our ancestors. One plant that has medicinal properties is green grass jelly (Cyclea barbata Miers). In this research, the extraction method used was maceration, with 96% ethanol solvent. The ethanol extract of green grass jelly leaves was screened for phytochemicals and tested for toxicity using the Brine Shrimp Lethality Test (BSLT) method. Toxicity tests were carried out at various concentrations of 100 ppm, 250 ppm, 500 ppm, 750 ppm and 1000 ppm. The results of the analysis of secondary metabolites contained in the ethanol extract of green grass jelly leaves are alkaloids, flavonoids, tannins and steroids. In the toxicity test, the highest average death percentage was obtained at the 1000 ppm extract concentration variation of 73.33%. From the probit and log concentration data, a linear regression equation y = was obtained with an LC 50 value of 558,25 ppm. This shows that the 96% ethanol extract of green grass jelly leaves (Cyclea barbata Miers) has toxic potential because the LC 50 value is in the range of 30-1000 ppm.